The Influence Of Work Discipline, Work Competence, And Work Abilities On Employees' Work Productivity At PT. Makmur Abadi Group - Muhammad Dio Saputra; Septa Diana Nabella; Muhammad Fadli Luran; Muhammad Rahmat; Andi Amang (Cita konsultindo, 2024)
An organization's success is contingent upon the productivity of its employees. This research was undertaken to assess the impact of work discipline, work competence, and work ability on employee productivity inside the firm. The duration of this study, employing quantitative methodologies, was a period of six months. Benefiting from a strong work ethic, high level of expertise, and exceptional job performance. The combined regression coefficients for work discipline (x1), work competency (x2), and work ability (x3) have a substantial impact on the work productivity variable (y).